Frontispiece: Enzymatic Late‐Stage Oxidation of Lead Compounds with Solubilizing Biomimetic Docking/Protecting groups. Issue 68 (13th December 2018) - Vickers, Clare; Backfisch, Gisela; Oellien, Frank; Piel, Isabel; Lange, Udo E. W.
Abstract : Combining biocatalytic oxidation with protective‐group chemistry enables one to modulate the site of oxidation. Lead compounds protected with different solubilizing biomimetic docking/protecting groups yield different hydroxylated derivatives with the same P450BM3 ‐mutant. Additional hydroxylation products are obtained when the P450BM3 ‐mutant is also varied. Derivatives of this type are difficult to obtain otherwise. Additionally, molecular‐dynamic simulations help to rationalize the observed oxidation patterns. For more information, see the Full Paper by U. E. W. Lange et al. onpage 17936 ff.